Meta-analysis to evaluate the effect of yeast as a feed additive on beef cattle performance and carcass traits - Torres, Rodrigo de Nazaré Santos [UNESP]; Paschoaloto, Josimari Regina; Júnior, Gercílio Alves de Almeida; Ezequiel, Jane Maria Bertocco [UNESP]; Coelho, Larissa de Melo; Neto, Otavio Rodrigues Machado [UNESP]; Almeida, Marco Tulio Costa (Elsevier, 2022)
Yeast (Saccharomyces cerevisiae) is a group of feed additives widely used in ruminant diets to improve rumen health and consequently animal performance. The present study evaluated the effect of yeast inclusion on beef cattle's performance and carcass traits by meta-analysis. We hypothesized that the variables experimental period, supply period, and statistical design affect beef cattle's performance and carcass traits supplemented with yeast. Thirty-one peer-reviewed publications with 106 treatment means were included in the data set. Yeast effect as an additive in beef cattle diets was evaluated by examining the weighted mean differences (WMD) between yeast treatment (diets with yeast inclusion as an additive) and control treatment (diet with no additive). Heterogeneity was explored by meta-regression and subgroup analysis using genetic group, experimental design, experimental period, yeast in diet (g/day), yeast type, feeding system, and concentrate in diet (g/kg of dry matter). The experimental period was the variable that most influenced the variability of responses with yeast in the diet. Yeast addition in the diets increased average daily gain (ADG; WMD= 0.03 kg/d; P = 0.001) and carcass weight (WMD=3.12 kg; P = 0.046). The experimental period and yeast supply for up to 90 days increased the animals’ final body weight. The effect of yeast inclusion in the diet on the variable final body weight was only affected by the inclusion period or yeast supply. For the other ADG, carcass weight, and dressing, the response's variation was dependent only on the level of yeast inclusion in the diet. The diet's inclusion levels between 10 and 15 g yeast/day increase average daily gain and carcass weight.
Keywords: Beef cattle; Carcass; Probiotics; Yeast